Helden müssen sterben : Von Sinn und Fragwürdigkeit des heroischen Todes - Hoff, Ralf von den; Brink, Cornelia; Falkenhayner, Nicole (2019)
"Heroes have to die because they are human. Their death, however, may vary in its relevance to their status as heroic figures. In Greek antiquity, death is the prerequisite for heroisation; expecting to continue their existence in the afterlife, martyrs sacrifice their lives in acts of killing that are often taken to the extreme; the war hero follows the call to commit his life to a greater good, without death being the necessary goal. Based on examples from the time between antiquity and the present age, the contributions to this book show from an interdisciplinary perspective how heroic action, dying, and death are respectively related to each other and how the representations of heroic dying mediate between heroes and their audience. The essays discuss questions such as: How do heroic figures die? What role does violence play in the process? How is the hero’s death presented and staged? What types of media in particular lend themselves to depictions of heroic death and the death of the hero? With contributions by Achim Aurnhammer, Cornelia Brink, Ulrich Bröckling, Jürgen Dendorfer, Nicolas Detering, Peter Eich, Nicole Falkenhayner, Andreas Gelz, Olmo Gölz, Joachim Grage, Barbara Korte, Dietmar Neutatz, Johanna Pink, Sitta von Reden, Anna Schreurs-Morét, Magnus Striet, Stefan Tilg, Ralf von den Hoff. "...